THE IMPACT OF MEDIA COVERAGE ON THE COURSE OF CRIMINAL PROCEEDINGS AND THE RIGHTS OF PARTICIPANTS - А.Ж. Муратова; И.С. Сактаганова; А.Б. Сактаганова; А.Е. Есеналиев; Р. Токанова (Хабаршы. Заң сериясы)
This article investigates the impact of media coverage on criminal trials and their participants, with particular attention paid to digitalization and social networks as sources of coverage. The purpose of the study is to analyze both legal and social aspects of interactions between media coverage and judicial system and make recommendations to minimize its negative influence. This work draws from a content analysis of media publications, comparative legal approach, and study of Kazakh and international judicial practice. The results indicated that excessive media coverage threatens presumption of innocence, compromises judicial independence, and induces psychological pressure among participants. As part of the contribution made, practical recommendations on media regulation were provided including standardization between media outlets and courts as well as offering practical advice to increase transparency and fairness during court proceedings.